Non-Electronic Transdermal Alcohol Biosensors - Hartman, Nickolas. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Fiorenzo Omenetto.; Committee: David Kaplan, and Charles Mace.; Keywords: Biomedical engineering, Biochemistry, and Public health.